Staff Wellbeing and Retention in Children's Social Work: Systematic Review of Interventions. (March 2022) - Turley, Ruth; Roberts, Sophie; Foster, Catherine; Warner, Nell; El-Banna, Asmaa; Evans, Rhiannon; Nurmatov, Ulugbek; Walpita, Yasaswi; Scourfield, Jonathan
Objective: To systematically review international evidence on the effectiveness and cost-effectiveness of interventions targeting the mental health, wellbeing, and retention of child and family social workers and their impact on child and family outcomes.Method: Systematic review and narrative synthesis of quantitative comparative studies. Published or unpublished research was sought via 12 bibliographic databases, websites, contact with experts, and citation tracking. Studies in any language were eligible for inclusion. Quality was assessed using Cochrane appraisal tools.Results: Fifteen studies were identified from 24 papers. Three studies considered individual-level interventions, with mixed and inconclusive findings. Eleven considered organisational interventions, with mixed but more promising findings. One study considered community-level interventions, with positive findings but a serious risk of bias. Only one study considered costs.Conclusion: The quality of evidence overall does not warrant clear recommendations for services. Organisation-level interventions show some promise. Robust, high-quality interventional studies are needed.